Gagasan Mahmud Muhammad Taha tentang Evolusi Syariah - M. Zayin Chudlori (Al-Qanun: Jurnal Pemikiran dan Pembaharuan Hukum Islam, 2008)
This article discusses the thought of Mahmud Muhammad Taha in methodology of istinbat or legal interpretation in ‎Islamic law which emphasizes on the egalitarian values of Islamic law. In his interpretation, he uses the naskh or ‎abrogation method, a method used by pioneering Islamic jurists to find solution for conflicting Qur’anic verses. It is ‎employed by applying the relevant verses revealed latter and postponing the application of other irrelevant verses. ‎However, Mahmud Muhammad Taha convinces that the abrogation method he has proposed is an enabling ‎method for the evolution of Islamic law. It is basically a flexible interpretation of the text that allows movement ‎from one Qur’anic text to another on the basis of relevance. As a result, the application of certain Qur’anic text and ‎abandonment of another is temporary and not conclusive. On other occasion, the abandoned text can be applied ‎whenever it becomes relevant. This study is based on egalitarian values of Islamic law which has been proposed by ‎Taha. He asserts that currently shari’ah or Islamic law is seen as discriminative and incapable of fulfilling the true ‎mission of Islam which is just, prosperous welfare and compassionate